Causes of Small Business Failure in Uganda: A Case Study from Bushenyi and Mbarara Towns 1 - Kazooba, Charles Tushabomwe (African Studies Quarterly, 2006)
Abstract: The privatization drive and the Civil and Public Service reforms that began in the early 1990s in Uganda laid a foundation for an increased number of small business enterprises. By 2002, small scale enterprises were employing approximately 2,000,000, and serving about 6,000,000 people at business and household level. The entrepreneurs that set up these enterprises lacked business management skills and capital, and as such, many of them faced a number of problems, most of which were of a startup nature. A survey was carried out to establish the causes of small business failures in Uganda using businesses in Mbarara and Bushenyi towns as case studies. In-depth interviews and questionnaire methods were mainly used to collect data from 133 small business enterprises. It is concluded that the causes of small businesses failure are multidimensional and diverse. They include poor management as well as political, economic, social, cultural and environmental factors. In practice, many of these are interrelated. The survey revealed that the startup factors posed a greater threat than those that are encountered once the business has been established. As such, business people who successfully negotiate the initial startup hurdles have greater chances of future success in their businesses. Despite the solutions sought over the years, the business community in Uganda is still hampered by the challenges. The study concludes by making a number of practical suggestions against business failure.
Keywords: Small Business; Uganda; small business enterprises